Ultrafine light-weight high-strength filler and preparation method thereof
By using composite nucleation agent and high-temperature melting process in light fillers, combined with segmented nucleation and crystallization treatment, ultrafine lightweight high-strength fillers with high strength, low water absorption and environmental protection are prepared, which solves the flammability, fragility and high water absorption of existing light fillers and has a wide range of application prospects.
Patent Information
- Application Number
- CN202411647954.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-18
AI Technical Summary
Existing lightweight fillers have disadvantages such as flammability, fragility, high water absorption and waste of mineral resources, and it is difficult to meet the requirements of high strength, low water absorption and environmental protection at the same time.
Ultrafine, lightweight, high-strength fillers are prepared by composite nucleation agent and high-temperature melting process. The uniform growth of grains is controlled through segmented nucleation and crystallization treatment to form high-strength spherical particles.
It has achieved sound absorption and noise reduction, fire resistance, light mass density, high compressive strength, low water absorption and ecological and environmentally friendly features, and is suitable for lime, gypsum and cement-based products.
Smart Images

Figure CN119638191A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fillers, and in particular relates to an ultra-fine, light-weight and high-strength filler and a preparation method thereof. Background Art
[0002] Lightweight filler is a filling material with low density and light weight. It has the advantages of light weight, heat preservation, sound insulation, easy construction, environmental protection and durability. It is often used in various insulation, sound insulation and filling fields.
[0003] Common lightweight fillers include polystyrene particles, expanded perlite, expanded vermiculite, vitrified microspheres, etc. Among them, polystyrene particles are a polymer material formed by the polymerization of monomers such as styrene. They have the characteristics of light weight, low density, and high strength. They are usually used in various thermal insulation materials, sound insulation materials, and filling materials. Expanded perlite is a new type of lightweight filler formed by the expansion of natural perlite after high temperature heating. It has the characteristics of low thermal conductivity, sound absorption and sound insulation, acid and alkali corrosion resistance, etc. It is widely used in thermal insulation, building decoration, road sound insulation and other fields. Expanded vermiculite is a natural vermiculite ore that is expanded by heating. It has the advantages of good sound absorption, heat insulation, and fire resistance. It is widely used in building insulation, fireproof and heat insulation, casting, metallurgy and other fields. Vitrified microspheres are a lightweight filler made of special raw materials expanded at high temperature. It has the advantages of fireproof, waterproof, non-toxic and tasteless. It is widely used in building exterior wall insulation, interior wall decoration and other fields.
[0004] In addition, there are lightweight fillers such as fly ash and lime, which are often used in projects such as embankment filling. They can effectively reduce the deadweight of new embankments, reduce embankment compression deformation, and improve embankment bearing capacity.
[0005] The lightweight fillers currently available on the market have more or less unavoidable shortcomings, such as the flammability of polystyrene particles, the fragility of expanded perlite, expanded vermiculite and vitrified microspheres, high water absorption and waste of mineral resources.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide an ultra-fine, lightweight and high-strength filler and a preparation method thereof. The filler has the characteristics of sound absorption and noise reduction, fire retardancy, light mass density, high compressive strength, low water absorption, and ecological environmental protection. It is suitable for lime, gypsum and cement-based products, especially in tile adhesives, lightweight plastering, self-leveling and other dry-mixed mortar products and sound-absorbing panels, sound insulation barriers, insulation panels, and fireproof board products. It has good application prospects.
[0008] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0009] The present invention provides an ultra-fine, light and high-strength material, which comprises 30-100 parts of quartz sand, 1-10 parts of broken glass, 1-15 parts of Al 2 O 3 , 7-15 parts Li 2 O, 2-8 parts P 2 O 5 , 1-12 parts ZrO 2 , 3-6 parts of composite nucleating agent, 5-10 parts of carbonate, 10-20 parts of feldspar and 2-5 parts of sulfate.
[0010] Furthermore, the filler particle size is 0.1-5 mm, the cylinder pressure strength is 2-30 MPa, and the bulk density is 50-350 kg / m 3 , water absorption rate is less than 8%.
[0011] Preferably, the composite nucleating agent comprises V 2 O 5 and / or 2 O 5 More preferably, when the composite nucleus agent includes V 2 O 5 and Ta 2 O 5 When V 2 O 5 and Ta 2 O 5 The mass ratio is (0.2-1.5):(1-4.5).
[0012] The present invention also provides a method for preparing the ultrafine, lightweight and high-strength filler, comprising the following steps:
[0013] S1: Take 30-100 parts of quartz sand, 1-10 parts of broken glass, 1-15 parts of Al 2 O 3 , 7-15 parts Li 2 O, 2-8 parts P 2 O 5 , 1-12 parts ZrO 2 , 3-6 parts of the composite crystal nucleating agent are mixed evenly, melted at high temperature, clarified and cast in a mold to obtain a basic mixture.
[0014] Furthermore, the high temperature melting is: putting the mixed product into a crucible, heating it to 1100-1450° C. at 2-10° C. / min in a high temperature sintering furnace and melting it for 2-10 hours.
[0015] Preferably, the composite nucleating agent comprises V 2 O 5 and / or 2 O 5More preferably, when the composite nucleus agent includes V 2 O 5 and Ta 2 O 5 When V 2 O 5 and Ta 2 O 5 The mass ratio is (0.2-1.5):(1-4.5).
[0016] S2: The basic mixture is heated to 500-650°C at 2-10°C / min and kept warm for 2-5h for nucleation treatment; then the temperature is raised to 700-780°C at 10-15°C / min and kept warm for 1-4h for crystallization treatment; fine crystal nuclei can be formed in the basic mixture and grow into crystallites of a certain size. This step directly affects the strength of the final product.
[0017] S3: Grind the product of step S2 to a particle size of ≤1 μm, then add 5-10 parts of carbonate, 10-20 parts of feldspar and 2-5 parts of sulfate, and mix well to obtain a secondary mixture.
[0018] Optionally, the carbonate includes one or more of calcium carbonate, dolomite or sodium carbonate.
[0019] Optionally, the sulfate comprises calcium sulfate and / or sodium sulfate.
[0020] S4: adding a binder to the secondary mixture and then granulating the mixture to obtain a filler body.
[0021] Optionally, the binder includes one or more of water glass solution, polyvinyl alcohol, sodium carboxymethyl cellulose, starch or sodium hydroxymethyl cellulose.
[0022] Furthermore, the amount of the binder added is 0.05-0.2% of the total mass of the raw material components.
[0023] Optionally, the granulation is one of centrifugal spray granulation, pressure spray granulation or granulation pan granulation.
[0024] S5: After drying the filler green body, place it in a sintering furnace for sintering to obtain the filler green body.
[0025] Furthermore, the sintering temperature is 900-1500° C., and the sintering time is 30-120 min.
[0026] Compared with the prior art, the present invention obtains a basic mixture by adding a composite nucleating agent and melting at high temperature, and then nucleating and crystallizing at different heating rates and temperatures, so that the grains can be controlled to grow uniformly into a certain size, so that a high-strength product can be obtained while having high porosity and light weight. The spherical particles formed after granulation have micropores, low bulk density, and low water absorption. At the same time, inorganic materials are used to produce ultra-fine, lightweight, and high-strength fillers, which are environmentally friendly when sintered at high temperatures. The obtained filler is suitable for lime, gypsum, and cement-based products, especially in tile adhesives, lightweight plasters, self-leveling, and other dry-mixed mortar products and sound-absorbing panels, sound insulation barriers, insulation boards, and fireproof board products. There is good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a macroscopic physical picture of the ultrafine, lightweight, high-strength filler of Example 1 of the present invention;
[0029] Figure 2 This is a light microscope internal structure diagram of the ultrafine, lightweight, high-strength filler of Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A method for preparing an ultrafine, lightweight, high-strength filler comprises the following steps: mixing 60 parts of quartz sand, 5 parts of broken glass, and 10 parts of Al 2 O 3 , 10 parts Li 2 O, 5 parts P 2 O 5 , 5 parts ZrO 2, 5 parts of composite nucleation agent are mixed evenly, put into a crucible, heated to 1300°C at 5°C / min in a high-temperature sintering furnace for 5 hours, and cast into a mold after clarification to obtain a basic mixture. The composite nucleation agent includes V 2 O 5 and Ta 2 O 5 .
[0033] The basic mixture was heated to 550°C at 5°C / min and kept at this temperature for 3 hours; then the temperature was raised to 750°C at 12°C and kept at this temperature for 2 hours. Subsequently, the product was ground to a particle size of ≤1μm. Then 10 parts of calcium carbonate, 20 parts of feldspar and 5 parts of sodium sulfate were added and mixed evenly to obtain a secondary mixture.
[0034] A water glass solution with a total mass fraction of 0.05% of the above raw materials was added to the secondary mixture, and granulated in a granulation pot to obtain a filler blank, which was then placed in a sintering furnace and sintered at 1150°C for 60 minutes. After cooling, a particle size of 0.1-5 mm and a bulk density of 0.4 g / cm 3 , a spherical ultrafine light-weight high-strength filler with a cylinder pressure strength of 18MPa and a water absorption rate of 3%. Its macroscopic and microscopic morphologies refer to Figure 1 and Figure 2 .
[0035] Example 2
[0036] A method for preparing an ultrafine, lightweight, high-strength filler comprises the following steps: mixing 65 parts of quartz sand, 3 parts of broken glass, and 8 parts of Al 2 O 3 , 8 parts 2 O, 8 parts P 2 O 5 , 2 parts ZrO 2 , 6 parts of composite nucleation agent are mixed evenly, put into a crucible, heated to 1450℃ in a high temperature sintering furnace at 5℃ / min for 2h, and cast into a mold after clarification to obtain a basic mixture. The composite nucleation agent includes V 2 O 5 and Ta 2 O 5 .
[0037] The basic mixture was heated to 650°C at 5°C / min and kept at this temperature for 2 hours; then the temperature was raised to 780°C at 15°C and kept at this temperature for 1.5 hours. Subsequently, the product was ground to a particle size of ≤1μm. Then 8 parts of calcium carbonate, 15 parts of feldspar and 3 parts of sodium sulfate were added and mixed evenly to obtain a secondary mixture.
[0038] 0.2% of the total mass fraction of the above raw materials was added to the secondary mixture, and the filler green body was obtained by spray granulation through a pressure granulator, and then placed in a sintering furnace for sintering at 1200°C for 70 minutes. After cooling, the particle size was 0.1-5mm and the bulk density was 0.2g / cm 3 , spherical ultra-fine lightweight high-strength filler with a cylinder pressure strength of 15MPa and a water absorption rate of 1%.
[0039] Example 3
[0040] A method for preparing an ultrafine, lightweight, high-strength filler comprises the following steps: mixing 55 parts of quartz sand, 10 parts of broken glass, and 5 parts of Al 2 O 3 , 15 Li 2 O, 2 parts P 2 O 5 , 8 parts ZrO 2 , 5 parts of composite nucleus agent are mixed evenly, put into a crucible, heated to 1200℃ in a high temperature sintering furnace at 5℃ / min for 5h, and cast into a mold after clarification to obtain a basic mixture. The composite nucleus agent includes V 2 O 5 and Ta 2 O 5 .
[0041] The basic mixture was heated to 500°C at 3°C / min and kept at this temperature for 5 hours; then the temperature was raised to 700°C at 10°C and kept at this temperature for 4 hours. Subsequently, the product was ground to a particle size of ≤1μm. Then 5 parts of calcium carbonate, 10 parts of feldspar and 2 parts of sodium sulfate were added and mixed evenly to obtain a secondary mixture.
[0042] Add 0.08% polyvinyl alcohol of the total mass fraction of the above raw materials to the secondary mixture, centrifugal spray granulation to obtain filler green body, then put it into the sintering furnace for sintering at 1000℃ for 80min, and after cooling, obtain the particle size of 0.1-5mm and the bulk density of 0.45g / cm 3 , spherical ultra-fine lightweight high-strength filler with a cylinder pressure strength of 16MPa and a water absorption rate of 5%.
[0043] Example 4
[0044] A method for preparing an ultrafine, lightweight, high-strength filler comprises the following steps: mixing 65 parts of quartz sand, 3 parts of broken glass, and 15 parts of Al 2 O 3 , 7 parts 2 O, 3 parts P 2 O 5 , 2 parts ZrO 2, 5 parts of composite nucleation agent are mixed evenly, put into a crucible, heated to 1200°C at 5°C / min in a high-temperature sintering furnace for 5 hours, and cast into a mold after clarification to obtain a basic mixture. The composite nucleation agent includes V 2 O 5 and Ta 2 O 5 .
[0045] The basic mixture was heated to 600°C at 5°C / min and kept at this temperature for 5 hours; then the temperature was raised to 750°C at 12°C and kept at this temperature for 4 hours. Subsequently, the product was ground to a particle size of ≤1μm. Then 10 parts of calcium carbonate, 16 parts of feldspar and 4 parts of sodium sulfate were added and mixed evenly to obtain a secondary mixture.
[0046] Add 0.05% polyvinyl alcohol of the total mass fraction of the above raw materials to the secondary mixture, centrifugal spray granulation to obtain filler green body, then put it into the sintering furnace for sintering at 1200℃ for 60min, and after cooling, obtain the particle size of 0.1-5mm and the bulk density of 0.15g / cm 3 , spherical ultra-fine lightweight high-strength filler with a cylinder pressure strength of 20MPa and a water absorption rate of 1%.
[0047] It can be seen that in Example 4, V 2 O 5 and Ta 2 O 5 The ratio of is 1:2.8, and the crystal nuclei generated by the staged sintering process at 600℃ and 750℃ are uniform, and self-assemble into fine and uniform microcrystals with higher strength. Compared with Examples 1-3, the bulk density, cylinder pressure strength and water absorption rate have significant advantages.
[0048] Comparative Example 1
[0049] A method for preparing a lightweight filler, which is different from Example 1 in that no composite nucleating agent is added. The obtained filler product has a particle size of 0.1-5 mm and a bulk density of 0.38 g / cm 3 , cylinder pressure strength is 4MPa and water absorption rate is 10%.
[0050] Comparative Example 2
[0051] A method for preparing a lightweight filler, which is different from Example 1 in that the base mixture is directly heated to 750°C at 5°C / min and kept warm for 2 hours. Then grinding and subsequent steps are performed. The obtained filler product has a particle size of 0.1-5mm and a bulk density of 0.41g / cm 3 , cylinder pressure strength is 7MPa and water absorption rate is 5%.
[0052] Table 1 Comparison of performance of different fillers
[0053]
[0054] It can be seen from Table 1 that in terms of the thermal conductivity of the material itself, EPS particles have the lowest thermal conductivity, less than 0.05 W / mk, followed by perlite, vermiculite and the products of Examples 1 to 4. Expanded clay has the highest thermal conductivity, above 0.1 W / mk.
[0055] Among several materials, except EPS particles which are not fire-resistant, the other lightweight materials are all non-combustible materials.
[0056] In terms of bulk density, EPS particles have the lowest bulk density, which is 15-50kg / m 3 , followed by expanded perlite, with a bulk density of 39-95kg / m 3 , the bulk density of the expanded clay and the products of Examples 1-4 is higher.
[0057] In terms of anti-ultraviolet stability, the inorganic materials expanded perlite, vermiculite, expanded clay and the products of Examples 1-4 all have the ability to resist ultraviolet rays, while the EPS particles do not have anti-ultraviolet stability.
[0058] In terms of particle appearance, expanded perlite is irregular particles with edges and rough surface; expanded vermiculite is brown or golden flaky particles with dull and rough surface; EPS particles are round spherical particles with smooth surface and easy to generate static electricity; expanded clay is spherical particles or crushed particles with rough surface; the products of Examples 1-4 are regular spherical particles with micropores on the surface.
[0059] In terms of compression resistance, expanded perlite is brittle and has poor compression resistance, followed by vermiculite and EPS particles; the products of Examples 1-4 have high compression resistance, and expanded clay has the highest compression resistance.
[0060] In terms of volume water absorption, expanded perlite has the highest volume water absorption, ranging from 50% to 70% depending on the degree of density; expanded vermiculite also has a volume water absorption between 50% and 70%; expanded clay is 5% to 15%; EPS particles and the products of Examples 1-4 have lower volume water absorption, which are 1-2% and 1-5%, respectively.
[0061] Taking all aspects of physical properties into consideration, perlite, vermiculite, EPS particles and expanded clay all have shortcomings, while the products of Examples 1-4 can still provide high compressive resistance, low water absorption and thermal conductivity at low bulk density, and have high UV resistance stability and non-flammability.
[0062] The products of Examples 1-4 are applied to other products and have the following advantages: low density, high compressive strength, high thermal insulation, non-flammability, alkali resistance, suitable for lime and cement-based products, spherical particles, easy construction, excellent sound absorption, solvent-free and odorless, and does not provide an environment for the growth of parasites and fungi.
[0063] Table 2 Performance comparison of examples and comparative examples
[0064]
[0065] It can be seen from Table 2 that in Comparative Example 1, no composite nucleus agent is added, and a microcrystalline structure cannot be formed, resulting in a product with many structural defects, greatly reduced strength, and high water absorption while being lightweight.
[0066] Comparative Example 2 did not use segmented nucleation and crystallization. Since the nucleation and growth processes were not controlled, fewer grains were formed and the size was uneven, and the strength could not be effectively improved. As a result, the strength was improved, but it was still at a low level.
[0067] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. An ultra-fine, lightweight, high-strength filler, characterized in that: In parts by weight, it includes 30-100 parts of quartz sand, 1-10 parts of broken glass, 1-15 parts of Al2O3, 7-15 parts of Li2O, 2-8 parts of P2O5, 1-12 parts of ZrO2, 3-6 parts of composite nucleating agent, 5-10 parts of carbonate, 10-20 parts of feldspar and 2-5 parts of sulfate.
2. The ultrafine, lightweight, high-strength filler according to claim 1, characterized in that: The filler particle size is 0.1-5mm, the cylinder pressure strength is 2-30MPa, and the bulk density is 50-350kg / m 3 , water absorption rate is less than 8%.
3. The ultrafine, lightweight, high-strength filler according to claim 1, characterized in that: The composite nucleating agent includes V2O5 and / or Ta2O5; Preferably, when the composite nucleus agent includes V2O5 and Ta2O5, the mass ratio of V2O5 to Ta2O5 is (0.2-1.5):(1-4.5).
4. A method for preparing the ultrafine, lightweight, high-strength filler according to any one of claims 1 to 3, characterized in that: The steps include: S1: According to weight, 30-100 parts of quartz sand, 1-10 parts of broken glass, 1-15 parts of Al2O3, 7-15 parts of Li2O, 2-8 parts of P2O5, 1-12 parts of ZrO2, and 3-6 parts of composite nucleating agent are mixed evenly, melted at high temperature, clarified, and cast in a mold to obtain a basic mixture; S2: heating the basic mixture to 500-650°C at 2-10°C / min and keeping it warm for 2-5h; then heating it to 700-780°C at 10-15°C and keeping it warm for 1-4h; S3: Grind the product of step S2 to a particle size of ≤1 μm, add 5-10 parts of carbonate, 10-20 parts of feldspar and 2-5 parts of sulfate, and mix well to obtain a secondary mixture; S4: adding a binder to the secondary mixture and granulating the mixture to obtain a filler body; S5: drying the filler green body and then sintering it to obtain the filler green body.
5. The preparation method according to claim 4, characterized in that: In step S1, the high temperature melting is as follows: the mixed product is placed in a crucible, and the temperature is raised to 1100-1450° C. at 2-10° C. / min in a high temperature sintering furnace for melting for 2-10 hours.
6. The preparation method according to claim 4, characterized in that: In step S3, the carbonate includes one or more of calcium carbonate, dolomite or sodium carbonate; And / or, the sulfate comprises calcium sulfate and / or sodium sulfate.
7. The preparation method according to claim 4, characterized in that: In step S4, the binder includes one or more of water glass solution, polyvinyl alcohol, sodium carboxymethyl cellulose, starch or sodium hydroxymethyl cellulose.
8. The preparation method according to claim 7, characterized in that: The amount of the binder added is 0.05-0.2% of the total mass of the raw material components.
9. The preparation method according to claim 4, characterized in that: The granulation is one of centrifugal spray granulation, pressure spray granulation or granulation pan granulation.
10. The preparation method according to claim 4, characterized in that: The sintering temperature is 900-1500° C., and the sintering time is 30-120 min.
Citation Information
Cited By
Sound absorption material and preparation method thereof
CN120004586A
Sound-absorbing material and preparation method thereof
CN120004586B
Lightweight composite porcelain clay and preparation method thereof
CN121651871A